Near-complete whole-genome sequencing of two Burkholderia Pseudomallei strains harbouring novel molecular class d beta-lactamase genes, isolated from Malaysia - Zainulabid, Ummu Afeera; Mohamad Zain, Noriwanisyam; Arumugam, Janaki; Kamarudin, Norhidayah; Zainal Abidin, Muhammad 'Adil; Abd Mokti, Abdullah Shamshir; Nordin, Noorlina; Rakawi, Ahmad Faizal; Abdul Majid, Aman Shah; Ashok, Ganasekaran; Alex, Lourdes Francis; Dean Tay, Darren; et al. (American Society for Microbiology, 2022)
Here, we present two 7.1- and 7.3-bp near-complete genome sequences of Burkholderia pseudomallei strains of HTAA077 and HRPB058, isolated from a pus culture from a confirmed melioidosis patient at Hospital Tengku Ampuan Afzan, Kuantan, Malaysia, and from blood culture from a patient at Hospital Raja Permaisuri Bainun, Ipoh, Malaysia, using a Nanopore MinION instrument.